The movement of islam Revival in XX–XXI centuries: economical and political aspects (Journal of Oriental Studies, 2016)
The article provides a brief historical overview of events related to the revival of religious consciousness in the Islamic countries. Islamic revival is one of the most important social movements of the twentieth century, the phenomenon, which covers geographically Muslim countries from North Africa to Southeast Asia. And it’s evident that Islamic revival is part of the broader historical, political and economic transformations.